Circulating miR-183-5p levels are positively associated with the presence and severity of coronary artery disease - Lv, Dong; Guo, Yanfu; Zhang, Li; Li, Xia; Li, Guangping (Frontiers in Cardiovascular Medicine, 2023)
Background: Serum miR-183-5p levels are associated with carotid atherosclerosis, while less is known about the relationship between circulating miR-183-5p levels and stable coronary artery disease (CAD). Methods: In this cross-sectional study, consecutive patients with chest pain who underwent coronary angiograms from January 2022 to March 2022 at our center were enrolled. Those presenting acute coronary syndrome or had a prior CAD were excluded. Clinical presentations, laboratory parameters, and angiographic findings were collected. Serum miR-183-5p levels were measured using quantitative real-time polymerase chain reaction. CAD severity was displayed as the number of diseased vessels and further evaluated by the Gensini score system. Results: Overall, 135 patients (median age, 62.0 yrs; male, 52.6%) were included in the present study. Stable CAD was identified in 85.2% of the study population, with 45.9% having 1-vessel disease, 21.5% having 2-vessel disease, and 17.8% having 3-vessel or left main disease. Serum miR-183-5p levels were significantly increased in CAD patients with different severities than non-CAD patients (all adjusted p < 0.05). Serum miR-183-5p levels increased as tertiles of the Gensini score progressed (all adjusted p < 0.05). Importantly, serum miR-183-5p levels could predict the presence of CAD and 3-vessel or left main disease in the receiver operating characteristic curve analysis (both p < 0.01), and also in multivariate analysis adjusting for age, sex, body mass index, diabetes, hypersensitive-C-reactive protein (both p < 0.05). Conclusion: Serum miR-183-5p levels are independently and positively correlated with CAD presence and severity.